'Why do parrots talk?' co-investigation as a model for promoting family learning through conversation in a natural history gallery*. Issue 1 (2nd January 2018) - Harris, Emily; Winterbottom, Mark
Abstract: Research into how and what families learn in science museums and other informal science learning settings suggests that parent-child interactions play an important role in shaping children's learning experiences. Our exploratory case study set out to discover and analyse learning happening within family groups during a visit to a traditional museum natural history gallery. Research methods were influenced by a growing body of literature that looks for learning in family visitor talk. Conversations of 18 families were recorded as they explored a gallery after being introduced to six learning games which fostered a 'climate of inquiry' and which were designed to spark family dialogue. Our findings indicate that families adopt a range of interactional approaches for building meaning together in a museum gallery. These approaches fell along a spectrum that varied according to the level of co-investigation and co-operation between group members. We suggest that family learning could be supported in informal learning contexts through simple, low-cost learning strategies that encourage dialogue and co-investigatory behaviours.